2022
DOI: 10.15244/pjoes/144190
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon, Total Nitrogen and Their Densities of <i>Nitraria Tangutorum</i> Nebkhas at Different Succession Stages on the Edge of Ulan Buh Desert

Abstract: This study aimed to determine if the succession of Nitraria Tangutorum nebkhas could change soil nutrients in the Jilantai desert, Inner Mongolia. Four succession stages including rudimental stage (RUD), developing stage (DEV), stabilizing stage (STA) and degrading stage (DEG) were regarded as succession patterns. We collected 588 soil profile samples within a 0-100 cm depth from different succession stages of N. tangutorum nebkhas. We determined the vertical distributions of soil organic carbon (SOC), total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Nutrient content in the soil can significantly influence the N and P nutrient status of plant organs, changes in these nutrients within the plant can undeniably impact the process of salt ion transportation (Das et al, 2022;Wei et al, 2021). In this research, we observed a consistent pattern in the interrelationship between certain ecological stoichiometric traits and salt ion content in the three halophytes.…”
Section: Interaction Between Organ and Soil Factorssupporting
confidence: 58%
“…Nutrient content in the soil can significantly influence the N and P nutrient status of plant organs, changes in these nutrients within the plant can undeniably impact the process of salt ion transportation (Das et al, 2022;Wei et al, 2021). In this research, we observed a consistent pattern in the interrelationship between certain ecological stoichiometric traits and salt ion content in the three halophytes.…”
Section: Interaction Between Organ and Soil Factorssupporting
confidence: 58%